2018
DOI: 10.1080/03004279.2018.1496124
|View full text |Cite
|
Sign up to set email alerts
|

Play-based pedagogy under threat? A small-scale study of teachers’ and pupils’ perceptions of pedagogical discontinuity in the transition to primary school

Abstract: Nicholson, P.M. (2018). Play-based pedagogy under threat? A small-scale study of teachers' and pupils' perceptions of pedagogical discontinuity in the transition to primary school. Education 3-13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Transitions have been described variously as a bridge, a border crossing, a process of continuity and change (Howe, 2016; Nicholson, 2019). There were some areas of continuity across the transition in this study, such as creative activities, and ICT (Q1, Q2, Q4, Q7).…”
Section: Context Of Study and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transitions have been described variously as a bridge, a border crossing, a process of continuity and change (Howe, 2016; Nicholson, 2019). There were some areas of continuity across the transition in this study, such as creative activities, and ICT (Q1, Q2, Q4, Q7).…”
Section: Context Of Study and Methodsmentioning
confidence: 99%
“…This understanding of progression reflects persistent tensions between systems and cultures in the pre-school phase, where ECE is positioned as a space of play, and compulsory education, where school is positioned as a space of work (Henderson et al, 2016). Even though play has been identified as a ‘metaphorical bridge’ (Nicholson, 2019), the pedagogic transition from play to work typically begins during the final year or months of pre-school so that children are ‘made ready’ for school by experiencing more formalised adult-led activities (Fisher, 2022; Wood, 2019). Based on a systematic review of teachers’ views of play-based learning, Bubikova-Moan et al (2019) document concerns about achieving a balance between child-led and adult-led activities.…”
Section: Transitions and School Readiness – Policies And Practicesmentioning
confidence: 99%
“…The paper is set within the troubled space of the early years of primary schooling, a space in which researchers, educators and practitioners have been struggling for some years, trying to resolve a number of tensions between, for example, formal versus informal approaches to teaching and learning, play versus work, and child-initiation versus teacher-direction (Allee-Herndon et al, 2019, Wood 2014. Research has consistently shown that, while most early years teachers in the primary context are enthusiastic about the value of play for children's learning, they are often confused about how they might continue to captivate the interest and engagement of young children through the medium of play while still ensuring that they meet required academic curriculum goals and targets (Nicholson, 2018, Jay & Knaus, 2018. Indeed, some studies suggest that practitioners appear comfortable when promoting the social and emotional aspects of learning through the medium of play, but when it comes to more academic learning they struggle, finding it a much more complex task.…”
Section: Background Contextmentioning
confidence: 99%